The Impression of Logistic Management on Customer Satisfaction in Small and Medium Enterprises - Riski Delfi Nur Aisa; Ratih Hendayani (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2021)
Batam has its own regulations to regulate its area. It is part of the Free Trade Area making Batam a priority area for exports and imports. The purpose of this research is to find out whether there is an effect of Logistics Management on Customer Satisfaction in SMEs in the Free Trade Area during a decline in economic growth. In, collecting data, the researchers used an instrument in the form of a questionnaire whose respondents were business actors in Small and Medium Enterprises (SMEs) in Batam. There are 428 samples then used as data analysis, applying Simple Linear Regression Analysis Technique using SPSS as a data processing tool. The results shown in the form of Logistics Management have a significant effect on SME Customer Satisfaction in Batam when there is a decline in economic growth.